Meningkatkan Hasil Belajar Siswa Kelas VIII A SMP Negeri 26 Banjarmasin Dengan Menggunakan Model Quantum Teaching Pada Materi Ajar Tekanan - Nor Rahmawati; Mastuang Mastuang; Misbah Misbah (Universitas Lambung Mangkurat, 2017)
Low of student learning result in science researcher doing lesson because the students are rarely directly involved in learning. Therefore, research that aims to improve learning result. This research aimed to describe (1) teaching materialize, (2) students’ learning result in cognitive aspect and (3) student activity. The method used is a Kemmis & Mc Taggart classroom action research model, with each cycle countain of planning, implementation, observation, and reflection steps. The subjects of this research were 36 students of VIIIth A grade. Technique of data collecting is learning result test, observation sheets, and documentation. Results of this research shown that by applying quantum teaching model (1) teaching materialize on 1st cycle categorized good, on 2nd and 3rd cycles is excellent, (2) completeness of students learning result improve concucivelly individual completeness percentage on 1st, 2nd and 3rd cycles are 69,44%, 77,78% and 94.44%, (3) student activities improve in every aspect with good categorize, except aspects asking questions aspect to teaching, not relevan behavior and express opinion on 1st cycle is categorized good enough, but on 2nd and 3rd cycle improve with consecutivelly categorized good and excellent. The conclusion that to in order to improve students learning result of VIIIth A grade SMP Negeri 26 Banjarmasin can improved by using quantum teaching model on pressure subject.